Rédei symbols and arithmetical mild pro-2-groups - Gärtner, Jochen (Annales mathématiques du Québec, 2014)
Generalizing results of Morishita and Vogel, an explicit description of the triple Massey product for the Galois group $$G_S(2)$$GS(2)of the maximal 2-extension of $$\mathbb {Q}$$Qunramified outside a finite set of prime numbers $$S$$Scontaining 2 is given in terms of Rédei symbols. We show that certain mild pro-$$2$$2-groups with Zassenhaus invariant $$3$$3occur as Galois groups of the form $$G_S(2)$$GS(2). Furthermore, a non-analytic mild fab pro-$$2$$2-group having only $$3$$3generators is constructed.
Gesehen am 28.07.2020